136k views
5 votes
Simplify the expression by combining like terms:

Simplify the expression by combining like terms:-example-1
User Sylma
by
4.8k points

2 Answers

2 votes

Explanation:


1 + 5a + 7a^(2)+a+3\\

so you have
7a^(2)

5a + a = 6 a

and 1 + 3 = 4

Answer:
7a^(2) + 6a + 4

User Jan Pisl
by
5.3k points
2 votes

Answer:

7a² + 6a + 4

Explanation:

Now we have to,

→ Simplify the given expression.

The expression is,

→ 1 + 5a + 7a² + a + 3

Let's simplify the expression,

→ 1 + 5a + 7a² + a + 3

→ 7a² + 5a + a + 1 + 3

→ (7a²) + (5a + a) + (1 + 3)

→ 7a² + (6a) + (4)

7a² + 6a + 4

Hence, answer is 7a² + 6a + 4.

User Alese
by
4.2k points